Electrical, morphological, thermal and mechanical properties of low density polyethylene/zinc oxide nanocomposites prepared by melt mixing method - Yamak, Hale Berber; Altan, Mihrigul; Altindal, Ahmet (NATL INST OPTOELECTRONICS, 2016)
In this study, low density polyethylene/zinc oxide (LDPE/ZnO) nanocomposites were prepared at different concentrations of ZnO nanoparticles, ranged from 0 to 36 wt%, by melt mixing method using twin-screw extruder in order to investigate the effect of presence and concentration change of nano-sized ZnO particles on the impedance spectra of LDPE and also on mechanical, thermal and morphological properties. Then, nanocomposite films with 170 micron thickness were obtained from the granulated nanocomposites by two-roll mills and hot pressing, respectively. Electrical properties of pure LDPE and LDPE/ZnO nanocomposite films were studied by impedance measurements over a temperature range of 298-400 K and in the frequency range from 50 Hz to 10 MHz. The room temperature conductivity evaluated from the straight-line fit in measured I-V plot and was found to be 1.3x10(-5) S cm(-1) and 4.7x10(-3) S cm(-1) for pure and 18% ZnO filled film, respectively. The results of impedance analysis showed that the inclusion of ZnO particles improved the dielectric properties of the samples. It was also observed that loss tangent increased as the frequency increased and reached a maximum and thereafter decreased. The thermal degradation temperatures of the LDPE showed an increase with presence and increasing content of the ZnO in LDPE. It was also determined that the tensile strength of the pure LDPE raised from 8.01 MPa to 8.60 MPa with the addition of ZnO nano particles but on the contrary, the elongation (%) of nanocomposites decreased apparently from 1.63 to 0.16.
Keywords: Dielectric property; Polymer nanocomposite; Nano-sized ZnO; LDPE; ZINC-OXIDE; DIELECTRIC-PROPERTIES; ZNO NANOPARTICLES; POLYMER COMPOSITES; OPTICAL-PROPERTIES; BEHAVIOR; MICROSTRUCTURE; CONDUCTIVITY; CONSTANT; WHISKER; Materials Science; Optics